2004
DOI: 10.1084/jem.20031110
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Virus-specific T Cells into Leukemia-reactive T Cells Using T Cell Receptor Gene Transfer

Abstract: T cells directed against minor histocompatibility antigens (mHags) might be responsible for eradication of hematological malignancies after allogeneic stem cell transplantation. We investigated whether transfer of T cell receptors (TCRs) directed against mHags, exclusively expressed on hematopoietic cells, could redirect virus-specific T cells toward antileukemic reactivity, without the loss of their original specificity. Generation of T cells with dual specificity may lead to survival of these TCR-transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
144
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 34 publications
(29 reference statements)
1
144
0
Order By: Relevance
“…Immunogens used to date are alloantigen 8 in mouse cells, and Epstein-Barr (virus) EBV 27 and cytomegalovirus (CMV) 28 and influenza virus 29 in human cells. Importantly, the potential utility of dual-specific T cells was highlighted by the demonstration of tumor inhibition in mice using mouse dual-specific T cells recognizing alloantigen and the ovarian cancerassociated antigen FBP.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogens used to date are alloantigen 8 in mouse cells, and Epstein-Barr (virus) EBV 27 and cytomegalovirus (CMV) 28 and influenza virus 29 in human cells. Importantly, the potential utility of dual-specific T cells was highlighted by the demonstration of tumor inhibition in mice using mouse dual-specific T cells recognizing alloantigen and the ovarian cancerassociated antigen FBP.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that TCRtransferred T-cell clones can have different expression levels of the introduced TCR, explaining the observed variation in cytolytic activity. 19 Different TCR expression levels might arise due to differences in the expression levels of the retrovirally encoded TCRab chains or competition for cell surface expression with the endogenous TCR and mixed TCR dimers. Based on the potent cytolytic effector function of CD8 + T cells, we hypothesized that T cells with higher antigenspecific cytolytic activity could be obtained by transferring the DBY-TCR to CD8 + CTL.…”
Section: Discussionmentioning
confidence: 99%
“…Since the specificity of the mixed TCR dimers is unknown, autoreactivity cannot be excluded. 19,32 The number of T cells with different TCR chains and thus the chance to generate autoreactive T cells can be limited by TCR gene transfer to T cells with defined antigen specificity. We previously demonstrated the reprogramming of cytomegalovirus (CMV)-specific T cells into leukemia-reactive T cells by transferring a TCR specific for the mHag HA-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations